Investigating Teacher–Student Interaction Patterns Between an Indonesian Pre-Service Teacher and Thai EFL Students - Mise Kania Septi; Fakry Hamdani; Muhammad Aminuddin (Lembaga Bale Literasi, 2026)
As globalization and regional mobility continue to reshape English language education, international teaching practicums have become important spaces for developing transformative pedagogical competence, intercultural communication, and learner-centered interaction. This study investigates teacher–student interaction patterns between an Indonesian pre-service teacher and Thai Grade 12 EFL students during a cross-cultural teaching practicum. Employing a qualitative descriptive design, data were collected from 770 interactional units through video recordings and non-participant observation, then analyzed using the Flanders Interaction Analysis System (FIAS). The findings revealed that student talk (44.94%) slightly exceeded teacher talk (42.73%), while classroom discourse was characterized by a semi-interactive and teacher-structured format. These results indicate that, despite linguistic and cultural differences, the pre-service teacher was able to foster meaningful classroom participation and collaborative engagement. The study highlights the transformative potential of international practicum experiences in preparing future English teachers to manage multilingual classrooms, negotiate intercultural communication, and promote active learning. It also extends the application of FIAS to intra-ASEAN EFL contexts and offers pedagogical implications for teacher education programs seeking to strengthen globally responsive and context-sensitive English language instruction.